KEGIATAN FISIOTERAPI KOMUNITAS PADA PASIEN BELL’S PALSY DI REHAB MEDIK RSUD PROVINSI NUSA TENGGARA BARAT - Rakhmad Rosadi; Suharni Raufe; Sri Sunaringsih Ika Wardojo; Tri Hutami Wardoyo; Nungki Marlian Yuliadarwati (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
The counseling was held aimed at providing education to patients and their families about bell's palsy, especially about the causes of bell's palsy and how to do independent exercises at home correctly to reduce complaints caused by patients. The method used is to provide counseling in the form of health promotion about Bell's Palsy to patients and their families as well as using leaflets as a media for counseling, giving pre-test and post-test in the form of questions to patients and their families to measure the effectiveness of the counseling provided to provide independent training at home. The counseling went well and was easily understood by the participants so that in the evaluation results there was an increase in participants' knowledge from 0% to 100% after the material was given and one of the participants also experienced quite good facial functional changes when given the application of physiotherapy management in the hospital using several modalities. Counseling activities can increase participants' knowledge about bell's palsy and there is a significant change where the value of facial muscle strength increases in patients with bell's palsy where the patient is able to speak